Improved Synthesis of the Antitubercular Agent SQ109 - Stampolaki, Marianna; Kolocouris, Antonios (SynOpen, 2021)
We present here an improved procedure for the preparation of the promising antitubercular drug SQ109 that is currently in phase Ib/III of clinical trials against Mycobacterium tuberculosis. We investigated and tested the literature synthetic procedure that enables the development of structure–activity relationships and report the observed inconsistencies as well as presenting improvements or novelties for the more efficient preparation of SQ109. Most significantly we applied a novel reduction step of the aminoamide precursor using Me3SiCl/LiAlH4 under mild conditions. These findings are important for research groups investigating the efficacy of this drug and analogues in academia and industry.
Keywords: SQ109; tuberculosis; synthesis; reduction; trimethylsilyl chloride; geranylamine; lithium aluminum hydride